A hybrid microfluidic system for regulation of neural differentiation in induced pluripotent stem cells. Issue 6 (11th March 2016) - Hesari, Zahra; Soleimani, Massoud; Atyabi, Fatemeh; Sharifdini, Meysam; Nadri, Samad; Warkiani, Majid Ebrahimi; Zare, Mehrak; Dinarvand, Rassoul
Abstract: Controlling cellular orientation, proliferation, and differentiation is valuable in designing organ replacements and directing tissue regeneration. In the present study, we developed a hybrid microfluidic system to produce a dynamic microenvironment by placing aligned PDMS microgrooves on surface of biodegradable polymers as physical guidance cues for controlling the neural differentiation of human induced pluripotent stem cells (hiPSCs). The neuronal differentiation capacity of cultured hiPSCs in the microfluidic system and other control groups was investigated using quantitative real time PCR (qPCR) and immunocytochemistry. The functionally of differentiated hiPSCs inside hybrid system's scaffolds was also evaluated on the rat hemisected spinal cord in acute phase. Implanted cell's fate was examined using tissue freeze section and the functional recovery was evaluated according to the Basso, Beattie, and Bresnahan (BBB) locomotor rating scale. Our results confirmed the differentiation of hiPSCs to neuronal cells on the microfluidic device where the expression of neuronal‐specific genes was significantly higher compared to those cultured on the other systems such as plain tissue culture dishes and scaffolds without fluidic channels. Although survival and integration of implanted hiPSCs did not lead to a significant functional recovery, we believe that combination of fluidic channels with nanofiber scaffolds provides a great microenvironment for neural tissue engineering, and can be used as a powerful tool for in situ monitoring of differentiation potential of various kinds of stem cells. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1534–1543, 2016.